Persepsi Masyarakat Terhadap Proses Layanan Kuitansi Elektronik di Kantor Pelayanan Kekayaan Negara dan Lelang (KPKNL) Surabaya - Fitri Nur Aini; Fitrotun Niswah; Meirinawati M; Eva Hany Fanida (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Post-auction services are a crucial stage that connects the entire transaction process, where delays or irregularities in signing receipts can cancel asset acquisition, BPHTB payments, and ownership transfers. This study aims to analyze the influence of public perception on the electronic receipt service process in terms of speed, transparency, and accountability. This research uses a variance-based Structural Equation Modeling (SEM) or Partial Least Square (PLS) model with SmartPLS 4.0. Data analysis consists of two stages of testing, namely the outer model and the inner model. The results show that the public's perception of the electronic receipt service process in terms of speed, transparency, and accountability is positive and significant. This indicates an increase in the public's positive perception of the speed, transparency, and accountability of the service, followed by a significant increase in the overall assessment of the electronic receipt service. Thus, the combination of service speed, service transparency, and service accountability will play a significant role in shaping public perception and increasing public satisfaction with the service provided.